e-Commerce Stock Inventory via ScanCart: The Android Barcode Scanner - Sharifah Saon; Abd Kadir Mahamad; Muzammil Mudzakir (Vol. 1 No. 1 (2019): Internet of Things: Tracking & Monitoring, 2022)
The usage of Android application was increased with the increment of smartphone per year, since user prefer internet to be one of the important infrastructure in their daily life. There are many applications for Android that has been released and some of them give great feedback in term of functionality and easy to used. Furthermore, it also very sustain in order to increase the productivity. Therefore, this is a great opportunity to create business based on mobile application. This project aims to develop an integrated Android barcode scanner with e-commerce system. This application allows user to scan a barcode and update quantity or create an order by using smartphone camera. Thus, the used of physical devices, were excessively reduced. Performances of developed Android application are evaluated based on survey by business and industrial partners.